Risk factors for alcohol use among pregnant women, ages 15-44, in the United States, 2002 to 2017 - Shmulewitz, Dvora (Prev Med, 2019)
Fetal alcohol exposure can lead to severe birth and developmental defects. Determining which pregnant women are most likely to drink is essential for targeting interventions. In National Survey on Drug Use and Health data on pregnant women from 2002–2017 (N=13,488), logistic regression was used to produce adjusted odds ratios (aOR) indicating characteristics associated with two past-month outcomes: any alcohol use and binge drinking. Risk factors were sociodemographic (age, race/ethnicity, marital status, education level, income) and clinical (trimester, substance use, alcohol use disorder, major depression). Where associations differed by pregnancy stage (trimester 1 vs. trimesters 2 and 3), association was evaluated by stage. Overall, higher risk for any and binge drinking was observed among those with other substance use (aORs 2.9–25.9), alcohol use disorder (aORs 4.5–7.5), depression (aORs=1.6), and unmarried women (aORs 1.6–3.2). For any drinking, overall, higher risk was observed in adolescents (aOR=1.5) and those with higher education (aOR=1.4), while lower risk was observed in those with lower income (aORs=0.7). For binge drinking, associations differed by pregnancy stage. In trimester 1, lower risk was observed in middle ages (aOR=0.4). In trimesters 2/3, higher risk was observed in Blacks (aOR=3.3) and those with lower income (aORs 3.5–3.9), while lower risk was observed in those with higher education (aOR=0.3). To prevent severe prenatal harm, health care providers should focus on women at higher risk for binge drinking during pregnancy: women with tobacco or drug use, alcohol use disorder, or depression, and women who are unmarried, Black, or of lower socioeconomic status.